FRI0483 INTEREST OF A SYSTEMATIC SCREENING OF OSTEOPOROSIS IN HEART TRANSPLANT PATIENTS. (June 2019) - Romain, CORALLI; Verdonk, Constance; Ottaviani, Sebastien; Goossens, Julia; Demaria, Lucie; Palazzo, Elisabeth; Dorent, Richard; Dieudé, Philippe; Forien, Marine
Abstract : Background: Osteoporosis is common among patients with end-stage heart disease. A rapid decrease of bone mineral density (BMD) is usually observed after heart transplantation. Bone loss is probably linked to glucocorticoids and calcineurin inhibitors use and vitamin D deficiency. Objectives: The aim of this study was to evaluate the interest of a systematic screening of osteoporosis in heart transplant patients. Methods: We performed a prospective monocentric study including patients, who had of heart transplantation in our hospital, from December 2016 to January 2019.The following parameters were systematically assesses: history of cardiac disease, immunosuppressive therapies, glucocorticoids, previous history of low trauma fracture, known risk factors of osteoporosis, treatment received for bone disease management (calcium, vitamin D and bisphosphonates). Blood tests with creatinine clearance, calcium and vitamin D levels, were assessed. Bone densitometry and spine radiographs (to search asymptomatic vertebral fractures) were assessed in all patients. Osteoporosis was defined respectively for patients ≥50 years and <50years as a T-score≤-2.5 SD and Z-score≤-2 SD either at lumbar spine (L2-L4), femoral neck or hip. Results: A total of 42 patients were included (76.7% male), mean age was 58.1±10.6 years, mean duration after transplantation was 2.6±3.1 years. Past or active smoking statues were observed in 26 patients (mean 23.9 pack-years). Calcium, vitamin D and bisphosphonates were administered in 13 (30.9%), 10 (23.8%) and one patients, respectively. All patients received prednisone (mean dose: 10.7±4.9 per day). Mean lumbar spine BMD was 1.03±0.25 g/cm 2 and left femoral neck BMD 0.85±0.15g/cm 2 . Osteoporosis was observed in 18 (45%) patients. Only one hip fracture was known before heart transplantation. Incidental low trauma fractures after transplantation were diagnosed in 14 patients (33.3%): 11 patients with vertebral fractures (mean 2 vertebral fractures per patient) including 4 patients with asymptomatic vertebral fractures. Others low trauma fractures were hip fracture, proximal humerus and fibula for one patient each. Mean duration between transplantation and the first low trauma fracture was 7.5±3.7 months. Low level of calcemia was found in 20 patients (47.6%) and low level of vitamin D (≤30mg/l) in 32 patients (76.2%) associated with secondary hyperparathyroidism in 21 patients (51.2%), mean creatinine clearance was 51.7±19.9ml/min. After evaluation, specific treatment of osteoporosis was started for 33 patients (78.6%): zoledronic acid (n=20), denosumab (n=8), alendronate (n=4) and teriparatide (n=1). Conclusion: Systematic screening of osteoporosis seems to be useful in heart transplant patients. Osteoporosis was observed in half of these patients with a high frequency of low trauma fracture after heart transplantation, particularly in the first year. Disclosure of Interests: None declared